Performance Evaluation of Fuzzy and PI Controller for Boost Converter with Active PFC - D. Lenine; Ch. Sai Babu; G. Shankaraiah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
In this paper, the problem of controlling AC-DC full bridge converter is considered. The control objectives are two, one is guaranteeing a regulated voltage for the connected load and second one is enforcing power factor correction (PFC) with input current sinusoidal. Power factor correction of Boost converter is done by using fuzzy control technique. The inner loop has a current error amplifier which improves the power factor by properly shaping the input current in accordance with its reference. This reference signal is always synchronized and proportional to the line voltage hence the input current comes in phase with the input voltage. Thus by improving the power factor maximum active power can be delivered to the load. The voltage loop is being controlled by the fuzzy controller and the multiplier. Voltage regulation is done by the fuzzy controller and input distortion is minimized by the fuzzy controller. The desired features of an active PFC technique are close to Unity Power Factor operation, less than 10 % total harmonic distortion in line current and simple control strategy. The fuzzy control technique gives better performance during different line voltage and load. The results are verified through MATLAB/Simulink.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.522